Requirement for the histone deacetylase Hdac3 for the inflammatory gene expression program in macrophages - Chen, Xuefen; Barozzi, Iros; Termanini, Alberto; Prosperini, Elena; Recchiuti, Antonio; Dalli, Jesmond; Mietton, Flore; Matteoli, Gianluca; Hiebert, Scott; Natoli, Gioacchino (Proceedings of the National Academy of Sciences - PNAS, 2012)
Histone deacetylases (HDACs) regulate inflammatory gene expression, as indicated by the potent antiinflammatory activity of pan-HDAC inhibitors. However, the specific contribution of each of the 11 HDAC proteins to the inflammatory gene expression program is unknown. Using an integrated genomic approach, we found that Hdac3-deficient macrophages were unable to activate almost half of the inflammatory gene expression program when stimulated with LPS. A large part of the activation defect was attributable to loss of basal and LPS-inducible expression of IFN-β, which maintains Stat1 protein levels in unstimulated cells and acts in an autocrine/paracrine manner after stimulation to promote a secondary wave of Stat1-dependent gene expression. Loss of Hdac3-mediated repression of nuclear receptors led to hyperacetylation of thousands of genomic sites and associated gene derepression. The up-regulation of the constitutively expressed prostaglandin endoperoxide synthase, Ptgs1 (Cox-1), a nuclear receptor target, had a causative role in the phenotype because its chemical inhibition reverted, albeit partially, the Ifn-β activation defect. These data indicate a central role for Hdac3 in inflammation and may have relevance for the use of selective Hdac inhibitors as antiinflammatory agents.